Large Group Housing Systems in Fattening Bulls—Comparison of Behavior and Performance - Schneider, Laura; Volkmann, Nina; Spindler, Birgit; Kemper, Nicole (Frontiers in Veterinary Science, 2020)
According to international housing recommendations, fattening bulls should not be housed in groups of more than 12 to 20 animals. However, there are no scientific studies supporting these recommendations as most studies on fattening cattle refer to smaller groups. Therefore, the aim of this study was to analyze and compare behavior and performance of 187 fattening bulls housed in different group sizes of 16, 22 and 33 animals. Behavioral observations were performed during three observation periods at an average age of 8.5, 13 and 17 months. Furthermore, body condition, health status and carcass weights were analyzed. Effects of increasing group size were observed regarding more synchronized lying behavior, longer lying durations and more undisturbed feeding and lying behavior. Interindividual variations in lying and feeding as well as mean and maximum percentages of animals participating simultaneously in interactions did not increase with group size. Health and growth performance were satisfactory in all group sizes. Therefore, the results of this study do not provide scientific evidence for the common argument that increasing group size leads to increased aggression. Furthermore, these findings indicate large group systems to be suitable for the housing of fattening cattle and to contribute to increasing animal welfare. Consequently, current recommendations should be revised.